Estilhaços : uma empatia animada - Gordeeff, Eliane Muniz (2017)
The purpose of this article is to analyze the use of hybridization of the animated and filmed image in the creation of a narrative that propitiates the empathy of the public. The work in question is the short film Fragments (2016), by the Portuguese animator José Miguel Ribeiro. The questions of variation of visual information and how the spectator receives these images are developed for the analyzes — through the works of George Sifanos (2012), of André Gaudreault and François Jost (1995) and of Marie-José Mondzaim (2015)